Analysis of Rainwater Harvesting (RWH) Capacity in Leuwigajah Urban-Village, South Cimahi - Mariana Marselina; Karina Indah Choirunnisa; Ery Nuralamsyah; Siti Ai Nurhayati (Universitas Diponegoro, 2022)
Leuwigajah Urban-Village is an area belonging to Citarum Watershed. Thus, it has a high potential to experience floods during the rainy season. Meanwhile, the area often experiences drought during the dry season due to high surface runoff and low infiltration. This paper discusses the capacity of RWH needed in N.A. of R.W. 19. It discusses hydrological conditions of the Cimahi watershed by presenting an analysis of rainfall data, land use data, and extreme discharge data, both maximum and minimum extreme discharges. Therefore, the Citarum Harum Community Service team decided to build Rainwater Harvesting (RWH) as a water supply source during the dry season. The RWH was built based on people's water needs 10 years later, from 2022-to 2032. Based on the calculations explained in the Rainwater Storage Module book issued by the Ministry of Public Works and Housing, the volume of RWH needed is 125 m3. However, due to limited land, it was decided to build an RWH with dimensions of 2 m x 2 m x 2 m which can accommodate 8 m3 of water. The water in this RWH can fulfil 6.4% of daily water needs, so it is recommended to be used for emergency purposes or secondary purposes such as agriculture and plantations.